Malaysian Society’s Appreciation for Nationhood Symbols in the Face of Industrial Revolution 4.0 Challenges: An Initial Observation - Haniffa, Mohamed Ali; Mohamad, Ayu Nor Azilah; Rambely, Nor Azlah Sham (ExcelingTech, 2020)
Abstract-This article discusses the importance of Malaysian society in appreciating the symbols of Malaysian nationhood. The symbols of Malaysian nationhood are the country’s Coat of Arms, National Anthems, National Flags, National Flowers and National Languages. It also discusses the appreciation and preparedness required by Malaysian society in sustaining the survival of Industrial Revolution 4.0. This article is a preliminary study conducted based on reading, observation and views. This study uses library resources. The findings based on the preliminary study indicate that Malaysians still have a low level of knowledge and sensitivity to the Malaysian national symbols. Keywords-Appreciation, Symbols of Malaysian nationhood, Nationalism, Identity, Industrial Revolution 4.0.